Hubungan Karakteristik Demografi Terhadap Pengetahuan SIBAT Di Bantaran Sungai Bengawan Solo - Triyono, Agung; Suhardono, Suhardono; Purnomo, Heru; Muawanah, Muawanah; Mudhofar, Muhamad Nor; Saptaningrum, Epi (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
ABSTRACTBackground: Climate change in Indonesia is strongly influenced by 3 basic climate patterns: monsoon, equatorial and local climate systems which cause dramatic differences in rainfall patterns, tending to give rise to a high potential for various types of hydrometeorological disasters, such as floods, flash floods, droughts, weather extreme, extreme waves. The community-based early warning system for flood disaster preparedness (SIBAT) is one of the means for preventing flood disasters.The aim of this research is to describeThe relationship between the characteristics of sibat cadres and knowledge about community-based early warning system strategies for flood disaster preparedness (sibat) on the banks of the Bengawan Solo River, Blora Regency. Research methods This is a quantitative approachcross sectional Â with a total sample of 110 SIBAT cadres selected using the Slovin method. Data was collected using a questionnaire sheet, then analyzed usingChi Square. The research results show that from3 The independent variable is significantly related to the dependent variable, the age variable with pvalue 0.013, gender variable with pvalue 0.071, education level variable with pvalue 0.013. which means that each variable has a strong relationship with the dependent variable, namely with knowledge about the Community-based Disaster Information System on the banks of the Bengawan Solo River.Keywords: SIBAT cadres, disaster preparedness, floods